Systemic Sclerosis – A Diagnostic Challenge or a Clinically Controllable Disease? - Olga Kądziołka; Karolina Skonieczna; Magdalena Badziąg; Paulina Szulc; Laura Kurczoba; Martyna Kłossowska; Olimpia Wiciun; Kacper Ordon (Quality in Sport)
Systemic sclerosis is a complex and heterogeneous autoimmune condition in which skin and internal organ involvement progresses through interrelated processes of vasculopathy, immune activation, and fibrosis. Although considered an uncommon disease, its impact is disproportionate due to delayed diagnosis and potential for multiorgan complications. This review aims to synthesize current knowledge on the underlying mechanisms, clinical spectrum, and management strategies of systemic sclerosis, with particular attention to validated classification criteria and therapeutic recommendations. The paper emphasizes the role of early clinical suspicion, specific serologic and capillaroscopic findings, and the significance of evolving immunomodulatory and antifibrotic therapies. An individualized and multidisciplinary approach remains essential in improving patient outcomes and quality of life.